Eco-labelling and environmental policy efforts in developing countries - Rasul Shams (Intereconomics, 1995)
Eco-labelling has become an increasingly popular instrument in recent years. Among the new developments which have been called for are that they should also be used as a means of encouraging developing countries to apply stricter environment policies. The following article investigates whether applying environmental seals of approval to the export products of developing countries is an efficient instrument for the purpose.
Keywords: 330; Environmental Protection